First Nations Youths' Experiences with Wellness: A Four Directions Approach - Warren, Jamie L (Scholarship@Western, 2013)
First Nations youth are a growing population at risk for multiple outcomes that affect their well-being. The effects of colonization and the residential school legacy continue to impact First Nations communities today, creating a cycle of intergenerational trauma to affect the next seven generations. As First Nations youth are at a social and economic disadvantage for maintaining balance in well-being, the purpose of this study was to identify through the Medicine Wheel teachings 1) what youth saw as contributors to well-being, 2) their vision for well-being, and 3) ways to achieve their vision. Using a qualitative approach, the results described the reality of wellness amongst First Nations youth in a holistic, cultural view. Face-to-face interviews were conducted with five First Nations youth in a rural First Nations community in Northern Ontario. Five themes emerged that were related to their experiences with wellness, including Balance Strategies and Challenges, Coping Strategies, Emotional Balance, Worldview, and Motivation, using a qualitative content analysis procedure. It was determined that the voices of First Nations youth are powerful, significant, and must be listened to. If an imbalance continues to affect the lives of First Nations youth, the imbalance will also be reflected in Canadian society. Further initiatives are needed to support and empower our First Nations youth on their journey to becoming tomorrow’s leaders.